Identification of the antibacterial action mechanism of diterpenoids through transcriptome profiling - Moon, Keumok; Hwang, Sungmin; Lee, Hyeon-Jeong; Jo, Eunhye; Kim, Jeong Nam; Cha, Jaeho (Frontiers in Microbiology, 2022)
Effective antibacterial substances of Aralia continentalis have anti-biofilm and bactericidal activity to the oral pathogen Streptococcus mutans. In this study, three compounds extracted from A. continentalis were identified as acanthoic acid (AA), continentalic acid (CA) and kaurenoic acid (KA) by NMR and were further investigated how these diterpenoids affect the physiology of the S. mutans. When S. mutans was exposed to individual or mixed fraction of diterpenoids, severe growth defect and unique morphology were observed. The proportion of unsaturated fatty acids in the cell membrane was increased compared to that of saturated fatty acids in the presence of diterpenoids. Genome-wide gene expression profiles with RNA-seq were compared to reveal the mode of action of diterpenoids. S. mutans commonly enhanced the expression of 176 genes in the presence of the individual diterpenoids, whereas the expression of 232 genes was considerably reduced. The diterpenoid treatment modulated the expression of genes or operon(s) involved in cell membrane synthesis, cell division, and carbohydrate metabolism of S. mutans. Collectively, these findings provide novel insights into the antibacterial effect of diterpenoids to control S. mutans infection, which causes human dental caries.